The Effects of an unexpected ceramic coating phase at the head of a pipe on joining and postprocessing of a ceramic-lined composite pipe - Mahmoodian, R.; Rahbari, R.G.; Abd Shukor, Mohd Hamdi; Hassan, Mohamed Mohsen Abdel-Naeim; Sparham, M. (Springer, 2013)
Produced ceramic-lined steel pipe using the self-propagating high-temperature synthesis (SHS) method has found uses in many applications. A SHS-centrifugal machine was designed to produce a ceramic-lined steel pipe from ferric oxide and aluminum powder (thermite mixture) under high centrifugal acceleration. The obtained products are expected to be Al2O3 ceramic in the innermost layer and a Fe layer in a region between the outer steel pipes. In the present work, specific regions of a pipe was particularly observed to investigate the stuck (dead) spaces at the pipe head because of its importance in further processes (joining, welding, etc.) which may affect the quality of the next operations. In this article, the product’s composition, phase separation, microhardness, and surface finish were studied on three zones of the pipe.